Correlation of Treg Prevalence and Function in Head and Neck Melanoma SLNs to Clinical Outcome. (23rd August 2013) - Ryan, Marisa A.; Crow, Jennifer; Fisher, Samuel R.; Lee, Walter T.; Proia, Alan
Abstract : Objectives: Sentinel lymph node (SLN) status is the most important prognostic factor in head and neck melanoma. Regulatory T cells (Tregs) are known to suppress tumor immunity. Indoleamine 2, 3‐dioxygenase (IDO) is an enzyme that promotes Tregs to become activated and promote tumor immune escape. Research objectives were to 1) assess Treg Prevalence and IDO in melanoma SLN and 2) correlate these scores with clinical outcome from patients with head and neck melanoma. Methods: Retrospective analysis of clinical and pathologic data of patients with SLN biopsy for head and neck melanoma between March 2004 and September 2011 at a tertiary medical center. Treg cells (CD4+C25+FoxP3+) and IDO were determined by immunohistochemistry. Specimens were scored to determine both intensity and prevalence of Treg and IDO positive cells. Scores were then correlated with clinical outcome using Fisher's exact test. Results: 26 total SLN were obtained, with 4 positive for melanoma. 22 SLN were negative for melanoma with 7 of 22 associated with poor patient outcomes (ie recurrence). All three SLN with high scores of Treg and IDO had poor outcomes. 23 SLN had either low Treg or IDO with 10 of 23 having both low. 4 of 23 were correlated with poor outcomes. There was a significant correlation of having high Treg and IDO levels with poor clinical outcome ( P = 0.014). Conclusions: FoxP3 and IDO expression in both positive and negative SLN may correlate with poor clinical outcome in head and neck melanoma.